2020
DOI: 10.1177/2233865919888364
|View full text |Cite
|
Sign up to set email alerts
|

Revisionist Conflict and State Repression

Abstract: What kinds of international conflicts make states more likely to increase repression? I argue that the issues at stake in conflict may have different levels of domestic salience and may alter the domestic political status quo, thus increasing or decreasing a state’s or regime’s propensity to repress. I argue and find that democracies are most likely to increase repression when they are territorial revisionists, specifically increasing the use of imprisonment and torture. Autocratic states are more likely to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 71 publications
(128 reference statements)
1
3
0
Order By: Relevance
“…To test these expectations, we employ mediation analysis. This reveals, on average, that governments facing an external threat do increase repression, aligning with prior findings (Davenport 2004(Davenport , 2007a(Davenport , 2007bDavenport and Armstrong 2004;Gibler 2012;Heffington 2020;Lebovic and Thompson 2006;Poe and Tate 1994;Poe, Tate, and Keith 1999;Wright 2014Wright , 2020. Notably, we find that longer periods of international conflict produce sharper increases, opening the door for domestic opposition.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…To test these expectations, we employ mediation analysis. This reveals, on average, that governments facing an external threat do increase repression, aligning with prior findings (Davenport 2004(Davenport , 2007a(Davenport , 2007bDavenport and Armstrong 2004;Gibler 2012;Heffington 2020;Lebovic and Thompson 2006;Poe and Tate 1994;Poe, Tate, and Keith 1999;Wright 2014Wright , 2020. Notably, we find that longer periods of international conflict produce sharper increases, opening the door for domestic opposition.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, international conflict can act exogenously, either by providing a boost in domestic political strength through a rallying effect, or by focusing repression on would be "fifth columns," opposition groups, or various groups of "others." International conflict is also more likely to lead to repression when the state perceives the conflict as threatening (Wright 2014(Wright , 2020Heffington 2020). 2 Perceptions of threat come from the conflict being lengthy, severe, and close to the state's capital as well as the regime believing that it will lose due to there being an unfavorable military asymmetry with the opponent.…”
Section: Interstate Conflict Domestic Repression Dynamics and The Opp...mentioning
confidence: 99%
See 1 more Smart Citation
“…Indirectly, external threats can reduce repression through the mediating variable of state capacity. We suspect that since these two paths lead to contradictory results, we can explain why previous empirical research, focused on interstate war and repression, found a weak or mixed relationship (Davenport 2007;Hill and Jones 2014;Wright 2020). To disentangle this relationship, we argue that capacity has a mediating relationship between external threats and state repression.…”
Section: The Direct and Indirect Effects Of External Threatsmentioning
confidence: 88%